Math
posted by Anonymous .
Multiply and Simplify:
(a^xa^(x))^3
=(a^xa^(x))(a^xa^(x))(a^xa^(x))
=(a^xa^(x))(a^2xa^0a^0+a^(2x))
=(a^xa^(x))(a^2x2+a^(2x))
=a^3x2a^x+a^(x)a^x+2a^(x)a^(3x)
=a^3x3a^x+3a^(x)a^(3x)
=???
Can you simplify down any further?
please and thank you

using the general
(ab)^3 = a^3  3a^2b + 3ab^2  b^3
(a^x  a^x)^3
= a^3x  3a^2xa^x + 3a^xa^2x  a^3x
= a^3x  3a^x + 3a^x  a^3x
Not sure where you want to go from here. 
It would be good as it is. If you want, you can replace
3a^(x) by 3/a^x and
a^(3x) by 1/a^(3x)
which may be considered more explicit.